2009
DOI: 10.1016/s0210-5691(09)70300-6
|View full text |Cite
|
Sign up to set email alerts
|

Eficacia y seguridad de la enoxaparina en la angioplastia primaria. Análisis comparativo con la heparina no fraccionada

Abstract: Objetivo. El objetivo de este estudio es comparar el efecto de la enoxaparina (ENX) y la heparina no fraccionada (HNF) intravenosas en la angioplastia primaria (AP) del infarto agudo de miocardio (IAMCEST).Diseño. Estudio prospectivo observacional. Pácientes y método. Se incluyó en el estudio a 191 pacientes con IAMCEST a los que se había realizado AP. En 91 (47,6%) se utilizó ENX y en 100 (52,4%), HNF. La elección del tratamiento se realizó a criterio del operador. Se excluyó a los pacientes con shock cardiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Three studies of PCI after fibrinolysis resulted in favorable outcome when enoxaparin was compared with UFH (LOE 4 397,432 ; LOE 5 394 ). Eight other studies showed no benefit using enoxaparin compared with UFH (LOE 2 342,433,434 ; LOE 4 405,409,435,436 ; LOE 5 345 ).…”
Section: Consensus On Sciencementioning
confidence: 97%
“…Three studies of PCI after fibrinolysis resulted in favorable outcome when enoxaparin was compared with UFH (LOE 4 397,432 ; LOE 5 394 ). Eight other studies showed no benefit using enoxaparin compared with UFH (LOE 2 342,433,434 ; LOE 4 405,409,435,436 ; LOE 5 345 ).…”
Section: Consensus On Sciencementioning
confidence: 97%
“…Enoxaparin can also be used with intravenous injections for immediate anticoagulation in patients undergoing primary percutaneous coronary intervention or elective percutaneous coronary intervention, as shown recently in several randomised studies 1112 13 14 Although studies have evaluated enoxaparin during percutaneous coronary intervention in several clinical settings,15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 none was powered for mortality.…”
Section: Introductionmentioning
confidence: 99%